An IL‐10 dominant polarization of monocytes is a feature of Indian Visceral Leishmaniasis. (30th May 2018) - Roy, S.; Mukhopadhyay, D.; Mukherjee, S.; Moulik, S.; Chatterji, S.; Brahme, N.; Pramanik, N.; Goswami, R. P.; Saha, B.; Chatterjee, M.
Summary: Leishmania donovani, the causative parasite of Visceral Leishmaniasis (VL), deviously manipulates host monocytes/macrophages to ensure its survival. Although monocytes/macrophages from patients with VL have demonstrated an impaired oxidative burst and antigen presentation, an unanswered yet pertinent question remains as to whether they are deactivated or alternatively activated. The significantly raised plasma levels of IL‐4/IL‐13 and IL‐10 in VL patients suggested a microenvironment conducive for alternative activation of monocytes/macrophages. Accordingly, the classical markers for IL‐4‐driven monocytes/macrophages [M(IL‐4)] were studied namely intramonocytic CD206 +, circulating CCL22 and CCL17, and were unchanged. Furthermore, the mRNA expression of Kruppel‐like factor 4 ( KLF4 ), peroxisome proliferator‐activated receptors ( PPAR )‐γ and arginase‐I ( ARG‐I ) in peripheral blood mononuclear cells was unaltered. However, markers for IL‐10‐driven monocytes/macrophages [M(IL‐10)], namely soluble CD163, intramonocytic IL‐10, and circulating CXCL13 were significantly increased. Monocytes/macrophages of patients with VL demonstrated an increased expression of markers for M(IL‐10), along with the absence of markers for M(IL‐4). Taken together, in human VL, manipulation of these IL‐10 polarized monocytes‐macrophages may pave the way for improved therapeutic outcomes.